La gestión del talento humano y su relación con los riesgos laborales del personal de enfermería en el área de cuidados intermedios del Hospital IESS de la ciudad de Milagro, provincia del Guayas. - Vásquez Espinoza, Gabriela de Jesús (2015)
The present research was to analyze the talent management and its relation to occupational hazards of nurses in intermediate care area IESS Hospital City Miracle, The methodology is scientific, descriptive. The scientist because through the conceptualization strategically locate the objectives, goals and values to establish the cause and effect of research in this paper. Field research for which the art, and as an instrument survey, the questionnaire structured and led to a statistically representative sample of 16 doctors, 24 nurses that make up the area plus 131 intermediate care area patients was used. With these results we proceeded to draw charts and graphs. Which states that the existing scenario evidence, conclusions and recommendations proposed committee Creating OHS-SSO-, replacing the Joint Committee on Safety and Health at Work, in order to be defined implemented the prevention of occupational risk sin professional practice which give security Nurses who work and users of the health service.